Сoncept of “Fourth generation of human rights”: attempt of philosophical and anthropological rationale - Vyacheslav A. Dolin (Антиномии, 2018)
This article is an attempt of philosophical and anthropological substantiation of the concept the “Fourth generation of human rights”, which develops the generational approach to the classification of human rights. Progress of convergent technology combining nano-, bio-, info- and cognitive technologies, is the objective basis for emergence of the analyzed concept. The methodological ground of the article is post-non-classical paradigm of human rights, and the anthropology of moderate bio-conservatism advocating for progressive development of technology against the human nature transformation. Convergent-technological and panhuman understanding of the concept of the “fourth generation of human rights” is identified based of conducted analysis. The submission on the fifth and sixth generations of human rights is refused through the application of “Occam's razor”. The fourth generation of human rights is associated with individual rights to influence current and further capabilities of convergent technologies to his or her own body but taking into account actual and potential limitations. In the article, the concepts of “human nature”, “corporality” and “freedom” are used for justification of analyzed concept from philosophical and anthropological standpoint. Their analysis allows us to formulate conclusions with methodological significance for understanding of the concept of the “fourth generation of human rights”. Firstly, it is the dialectical unity of constancy and change in human nature, which is understood as a multicomponent phenomenon. Secondly, it is the importance of human being as the evolutionary current corporality. Thirdly, it is the combination of voluntary refusal at individual level from potentially dangerous of the future of human technology and legal limitations of technology usage, the threat of which is regarded dangerous for community. The author criticizes the liberal anthropological understanding of the concept the “fourth generation of human rights”, which ignores the commonality with other people. These conclusions are substantiated with anthropology of moderate bio-conservatism; they constitute a conceptual limitation of implementation of somatic rights of person, which makes possible to synthesize the convergent-technological and panhuman understanding of the concept the “fourth generation of human rights”. The results of the research contributes to rationale of universal conception of human rights.